Strategies for Improving Workers’ Skills through Crafts Product Innovation - Ciptandi, Fajar (International Journal of Psychosocial Rehabilitation, 2020)
In this modern era, the demands on various innovations have become unavoidable things. The traditions in Indonesia are also required to bring innovation both in value, physical products, behavior and skills of its society. An example of this is the tradition of making traditional fabrics in Tuban, East Java, which is currently considered slow in presenting various innovations. For a long time, this tradition has not presented new positive values . It also showed the low novelty of its traditional products in the form of gedog woven fabrics. The main obstacle to this is because the characteristics of the people in Tuban tend to be conservative both in thinking and skills. Although some innovation efforts have been made, the craftsmen are considered not ready to change and break out of traditional patterns. Through an experimental approach, by referring to the theory of innovation diffusion, a process of incorporating innovation will be carried out in the form of developing gedog woven fabrics that involves craftsmen by dividing it into two groups, innovators and early adopters, while still adopting some of the existing traditional work patterns. Thus, a conclusion will be resulted in the form of an appropriate strategy to improve the work skills of craftsmen as well as producing an innovation on a traditional product in the form of woven fabrics in the form of new motif designs. This can also be a recommendation to be applied to other community groups in Indonesia who have a tradition similar to Tuban, East Java.